Effectiveness of Fig Leaf Ethanol Extract (Ficus carica L.) As An Antidiabetes In Alloxan-Induced Diabetes Model in Rats - Habibie, Muhammad Farhan; Ansyari, Dedi (Universitas Muhammadiyah Sumatera Utara, 2026)
Abstract: Long-term use of diabetes mellitus medication can cause several complications, so oter alternative treatments are needed that tend to have safer effects, such as herbal treatments using fig plants. Researchers feel the need to test with different doses and subjects to determine whether fig leaf extract (Ficus carica L.) is effective as an antidiabetic in alloxan-induced diabetic mouse models. This research uses a true experimental method with a pretest-posttest with control group design. Sampling used the simple random sampling method. The samples used were 36 male white rats (Rattus norvegicus L.), which were divided into 6 groups. Data will be analysed using the paired sample T test, one-way ANOVA test, and Post hoc test. The results showed that administering ethanol extract of fig leaves at doses of 200 mg/KgBW, 400 mg/KgBW, and 600 mg/KgBW had effectiveness as an antidiabetic in reducing fasting blood sugar levels in rats induced by alloxan (p = 0.000). However, only the ethanol extract group of fig leaves at a dose of 600 mg/kg bw (P3) had antidiabetic activity that was as effective as the drug glibenclamide (p = 0.253). Administration of ethanol extract of fig leaves (Ficus carica L.) has antidiabetic effectiveness in a rat model of alloxan-induced diabetes.